Determining the number of breaks in a piecewise linear regression model - Birgit Strikholm (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
In this paper we propose a sequential method for determining the number of breaks in piecewise linear structural break models. An advantage of the method is that it is based on standard statistical inference. Tests available for testing linearity against switching regression type nonlinearity are applied sequentially to determine the number of regimes in the structural break model. A simulation study is performed in order to investigate the finite-sample behaviour of the procedure and to compare it with other alternatives. We find that our method works well in comparison for both single and multiple break cases.
Keywords: C22; C51; 330; Model specification; multiple structural breaks; Mathematik; Strukturbruch